Correlated Color Temperatures of Fluorescent Lamps on the Basis of 10° Field Color Matching Functions and a Field Trial of the CIE Color Matching Functions - MORI, Leo; SUGIYAMA, Haruo; KAMBE, Naotake (Journal of the Illuminating Engineering Institute of Japan, 1964)
Correlated color temperature of a fluorescent lamp, because of its definition, changes with the change of the color matching functions. The correlated color temperatures of eight kinds of fluorescent lamps have been calculated for the 1931 and 1964 CIE color matching functions. The predicted change for a standard type warm white fluorescent lamp has been checked by a visual experiment in which 11 subjects matched a filtered tungsten lamp with the fluorescent lamp on the juxtaposed visual fields of 2°C and 10°C angular subtenses. The results of matchings accord well with those calculated from the CIE standard observer in average. In addition, a statistical discussion can not prove any difference between the results of the subjects in this experiment and those from the 1964 CIE standard observer. This paper also discusses the influence of the substitution of the y10γ function instead of Vγ on the photometric values. The maximum luminous efficiency is calculated as 654.5 [10° field-1m·W-1], and the photometric values of almost all the fluorescent lamps numerically increase.